2015
DOI: 10.1002/adfm.201503326
|View full text |Cite
|
Sign up to set email alerts
|

Plasmon‐Enhanced Fluorescence‐Based Core–Shell Gold Nanorods as a Near‐IR Fluorescent Turn‐On Sensor for the Highly Sensitive Detection of Pyrophosphate in Aqueous Solution

Abstract: Developing plasmon‐enhanced fluorescence (PEF) technology for identifying important biological molecules has a profound impact on biosensing and bioimaging. However, exploration of PEF for biological application is still at a very early stage. Herein, novel PEF‐based core–shell nanostructures as a near‐infrared fluorescent turn‐on sensor for highly sensitive and selective detection of pyrophosphate (PPi) in aqueous solution are proposed. This nanostructure gold nanorod (AuNR)@SiO2@meso‐tetra(4‐carboxyphenyl) p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
46
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 63 publications
(49 citation statements)
references
References 70 publications
3
46
0
Order By: Relevance
“…Recently, several works have reported that the result of investigations of the distance and plasmon wavelength dependent fluorescence of fluorophore via nanorod or nanoparticle substrate [85,86]. In particular, core-shell configuration, precisely controlling the distance between fluorophore and plasmonic nanostructure, have been widely used in the investigation of PEF effect recently [87][88][89][90]. It is found that by introduction of silica shell with various thicknesses to isolated fluorophore Au nanoparticles (AuNPs) and four different target molecules with different absorbance properties, the investigation of fluorescence quenching effect from complete quenching to no coupling was comprehensively carried out.…”
Section: The Wavelength and Spacer Effect Towards The Fluorescence Enmentioning
confidence: 99%
“…Recently, several works have reported that the result of investigations of the distance and plasmon wavelength dependent fluorescence of fluorophore via nanorod or nanoparticle substrate [85,86]. In particular, core-shell configuration, precisely controlling the distance between fluorophore and plasmonic nanostructure, have been widely used in the investigation of PEF effect recently [87][88][89][90]. It is found that by introduction of silica shell with various thicknesses to isolated fluorophore Au nanoparticles (AuNPs) and four different target molecules with different absorbance properties, the investigation of fluorescence quenching effect from complete quenching to no coupling was comprehensively carried out.…”
Section: The Wavelength and Spacer Effect Towards The Fluorescence Enmentioning
confidence: 99%
“…SiO 2 ‐Apt‐PrP Sc ‐BSNVA NPs are used as control sample because they do not affect the fluorescence of dyes, hence serving as a common method to observe PEF. [16c,26]…”
Section: Resultsmentioning
confidence: 98%
“…The enhanced local EM fields around plasmonic nanostructures can dramatically modify the optical properties of adjacent fluorescent molecules, known as PEF. [16a] PEF is considered as an attractive biosensing technique as it can improve detection sensitivity of target molecules. The plasmon metallic NPs are key factors in PEF because they can serve as antennas providing enhanced EM field .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations